ChemInform Abstract: Triphenylphosphine/Triethylamine‐Mediated Decarboxylation of α‐Oxocarboxylic Acids and Application in a One‐Pot Synthesis of Deuterated Aldehydes. Issue 22 (12th May 2016) - Niu, Guang‐Hao; Huang, Pei‐Ru; Chuang, Gary Jing
Abstract: A broad range of functionalized aryl α‐oxocarboxylic acids as well as hetaryl and alkyl substituted analogues serve as effective synthons for aldehydes which may be isolated in moderate to high yields.